Behavioral Challenges of Technology Adoption among Bank Employees: A TAM perspective - KATKE, DR. KADAMBINI (The journal of contemporary issues in business and government, 2021)
Technology transition is norm for any business survival and growth. Across the globe business environment doesn’t permit any leverage on technology adoption. The recent pandemic further made it mandatory for every organization to transform into technology enabled business operation. Many sectors were forced to adopt faster technology change to keep pace of business. Banking sector is no exception for this. After merging under single umbrella SBI has initiated technology transition and attempting to offer technology at fingertips both for its employees and customers. In recent press release SBI announced adoption of automation, AI and Machine learning in most of its back-end jobs for operational efficiency and cost advantage. These initiatives cannot be deployed in isolation; it has to have human interface to complete business process. And natural human response for any change is resistance. This is not easier transition rather this is continuous process with many challenges. The major issues are employees’ adoptability to the changing technology in the job performance. Individual perception and intentions are major determinant factors for any technology adoption. Technology Adoption Model elaborately explains human behavioral responses to new technology. Perceived usefulness and Perceived ease of use are two major attributes to the behavior intentions. This study attempts to test these attributes among bank employees with respect to implementation of information technology in banking service. Resistance for any change is human nature, but preparedness to overcome this resistance is need of hour for organizational and employee survival.